Biblijne aspekty bezdomności w przestrzeni artystycznej Zbrodni i kary Fiodora Dostojewskiego - Jankowska, Tatiana (Przegląd Rusycystyczny, 2011)
БИБЛЕЙСКИЕ АСПЕКТЫ БЕЗДОМЬЯ В ХУДОЖЕСТВЕННОМ ПРОСТРАНСТВЕ ПРЕСТУПЛЕНИЯ И НАКАЗАНИЯ ФЕДОРА ДОСТОЕВСКОГО Резюме В системе художественного пространства Достоевского функционирует мотив бездомья. Обусловленный контаминацией с секвенцией движения персонажа, мотив бездомья фигурирует как алегория изгнания и извечного скитания. На семиотическом уровне текста проявления этого мотива сопряжены с пространственной моделью дома Юрия Лотмана, основанной на тройной опозиции: дом–антидом–бездомность. Глубоко укоренившаяся в тексте библейская символика позволяет проследить мотив бездомья в трёх аспектах: Потерянного рая, Земли обетовенной и Вечного дома. BIBLICAL ASPECTS OF HOMELESSNESS IN THE ARTISTIC SPACE OF CRIME AND OUNISHMWNT BY FYODOR DOSTOYEVSKY Summary Dostoevsky’s artistic space presents peculiar functions of the motif of homelessness. It is conditioned by the contamination with the sequence of character’s movement, that appears as an allegory of banishment and constant wandering. on the semiotic level of the text, the function of this motif is connected with Yuri Lotman’s spatial model of home in terms of a triadic opposition: home–antihome–homelessness. The deep biblical imagery rooted in the textual system allows to examine the motif of homelessness in three aspects: paradise Lost, promised Land and eternal Home.